Antiviral activity of selected cathelicidins against infectious bronchitis virus. Issue 1 (31st May 2021) - Verheije, M. Hélène; Coorens, Maarten; Weerts, Erik A. W. S.; Berends, Alinda J.; van Harten, Roel M.; Angel, Marloes; Kooij, Jannetje; Ordonez, Soledad R.; van Beurden, Steven J.; van Dijk, Albert; Haagsman, Henk P.; Veldhuizen, Edwin J. A.
Abstract: Avian infectious bronchitis (IB) is a highly contagious disease caused by infectious bronchitis virus (IBV), a coronavirus of domestic fowl. IB is a major concern in the poultry industry, causing worldwide economic losses through decreased egg production and quality and by increasing the chicken's susceptibility for secondary bacterial infections, particularly Escherichia coli . In this study, the anti‐IBV activity of cathelicidins, small antimicrobial peptides of the innate immune system was investigated. The cell culture adapted (nonvirulent) IBV strain Beaudette was effectively inhibited by the human cathelicidin LL‐37 in bovine hamster kidney‐21 cells at nontoxic concentrations. The peptide needed to be present during virus inoculation to effectively inhibit the infection of IBV‐Beaudette, indicating that LL‐37 likely bound viral particles. However, no clear morphological changes in the IBV virion upon binding were observed by electron microscopy. In this cell culture model, chicken cathelicidins (CATH1‐3) were inactive against IBV‐Beaudette. In contrast, in multicellular infection models using the virulent IBV‐M41 strain the activities of human and chicken cathelicidins were different. In particular, upon inoculation of 10‐day‐old embryonic eggs with IBV‐M41, CATH‐2 reduced the viral load to a higher extend than LL‐37. Similarly, viral infection of chicken tracheal organ cultures with IBV‐M41 was significantly reduced in the presence of CATH‐2 but not LL‐37. These results indicate a potential antiviral role for CATH‐2 upon IBV infection in vivo . Abstract :